Relations between senses of work and job satisfaction: analysis of a public servants category - Ribeiro, Elisa Leonardi; Marra, Adriana Ventola (Revista de Administração da UFSM, 2021)
Purpose –This research had the aim to analyze if the senses of the work are able to influence the level of satisfaction of federal public servants. Design/methodology/approach – For that, a mixed approach study was carried out with the technical-administrative servants in education of a Federal University, based in countryside of Minas Gerais state. A total of 186 questionnaires were collected, using an adaptation of the Meaningful Work Scale (MWS) and the Work Satisfaction Scale (EST), and 10 semi-structured interviews were conducted. Findings –The correlation analyzes between the two constructs revealed the existence of moderated forces of association, for the most part, between the dimensions of the senses of work and the average score of work satisfaction, whereas linear regression revealed a genuine effect of the meanings of work on job satisfaction indexes. The content analysis of the interviews supported the results found, allowing to conclude that, for the servers surveyed, the identification with the work performed in an environment that values aspects such as ethics, autonomy, relationships and learning ends up influencing directly and positively the level of satisfaction with this job. Originality/value – Understanding the relationship meanings and work satisfaction of public servants, in the context of people management, presents itself as an original and valuable research, contributing to university managers to seek new ways of encouraging employees.